A scoping review of academic and grey literature on migrant health research conducted in Scotland - G. Petrie; K. Angus; R. O'Donnell (BMC, 2024)
Abstract Background Migration to Scotland has increased since 2002 with an increase in European residents and participation in the Asylum dispersal scheme. Scotland has become more ethnically diverse, and 10% of the current population were born abroad. Migration and ethnicity are determinants of health, and information on the health status of migrants to Scotland and their access to and barriers to care facilitates the planning and delivery of equitable health services. This study aimed to scope existing peer-reviewed research and grey literature to identify gaps in evidence regarding the health of migrants in Scotland. Methods A scoping review on the health of migrants in Scotland was carried out for dates January 2002 to March 2023, inclusive of peer-reviewed journals and grey literature. CINAHL/ Web of Science/SocIndex and Medline databases were systematically searched along with government and third-sector websites. The searches identified 2166 journal articles and 170 grey literature documents for screening. Included articles were categorised according to the World Health Organisation's 2016 Strategy and Action Plan for Refugee and Migrant Health in the European region. This approach builds on a previously published literature review on Migrant Health in the Republic of Ireland. Results Seventy-one peer reviewed journal articles and 29 grey literature documents were included in the review. 66% were carried out from 2013 onwards and the majority focused on asylum seekers or unspecified migrant groups. Most research identified was on the World Health Organisation's strategic areas of right to health of refugees, social determinants of health and public health planning and strengthening health systems. There were fewer studies on the strategic areas of frameworks for collaborative action, preventing communicable disease, preventing non-communicable disease, health screening and assessment and improving health information and communication. Conclusion While research on migrant health in Scotland has increased in recent years significant gaps remain. Future priorities should include studies of undocumented migrants, migrant workers, and additional research is required on the issue of improving health information and communication.